Peran Pendidikan Sebagai Sarana Pelestarian Budaya Sekitar Bagi Peserta Didik - Hilda Fahira; Dinie Anggraeni Dewi; Rizky Saeful Hayat (Jurnal Multidisiplin Indonesia, 2023)
The educational process cannot be separated from the culture that exists in a society. Therefore, the implementation of the educational process is not only a means to transfer knowledge to students, but is also used as a means to foster a sense of love for the country towards existing culture. Therefore, schools as places where the educational process is carried out have a very important role in the process of cultural preservation. Apart from that, schools must be able to be responsible in the process of students acquiring cultural values ​​around them so that they can cultivate self-authenticity which will become the nation's next generation. Schools can carry out various methods in the process of preserving culture for students, which can be done in learning activities or other activities outside of school.